IMPLEMENTASI KERJASAMA SISTER CITY KOTA BANDUNG - KOTA FORT WORTH DI BIDANG PENDIDIKAN - Intan Rodiah Gusman (Journal of Diplomacy and International Studies, 2020)
In the current era of globalization, all countries are required to build cooperation with other countries, the reason is that through the cooperation of one country with another country, they can connect with each other in order to realize a common goal in accordance with the interests of their respective countries. Therefore, cooperation is expected to create world peace, so that the dark tragedy that occurred during World War I and World War II does not repeat again. However, we need to know that the cooperation that is built is not only carried out by the central government, because the central government will not be able to handle overall cooperation in a country, therefore the government makes a policy to allow local governments to handle international cooperation with other countries with a system " Sister City” or cooperation between cities. This also happens because the world enters the era of paradiplomacy, where a collaboration can no longer be done only by the central government, but both local governments and other actors also participate in coloring the world of diplomacy today. Meanwhile, before a Regency / City wishes to establish a cooperative relationship with a city in another country, the local government must first report and request permission from the central government, namely through the Ministry of Foreign Affairs and also the Ministry of Home Affairs. Local governments as sub-state actors have currently used their authority to cooperate with local governments at the same level as in other countries to develop their regions. This is called sister city cooperation. Sister city cooperation is here to strive for regional development not only in the economic sector (profit) but also able to bring non-economic benefits such as in education and culture (benefits). This research uses a qualitative system, namely by taking sources from several references such as books, journals, articles, news and other sources related to the author's research. This study serves to analyze the ILA (International Leadership Academy) program as the success of the Bandung-Fort Worth Sister City Cooperation.